2017
DOI: 10.2320/matertrans.m-m2017807
|View full text |Cite
|
Sign up to set email alerts
|

Electrolysis Oxidation of Chalcopyrite and Molybdenite for Selective Flotation

Abstract: Electrolysis oxidation of chalcopyrite and molybdenite was investigated, via various electrochemical methods, with the aim of realizing selective otation of these minerals. Result of potential polarization indicated that oxidation via electrolysis affected only the chalcopyrite surface, owing mainly to the difference in conductivity of these minerals. Also measurements of contact angle after electrolysis indicated that contact angle of chalcopyrite selectively decreased whereas that of molybdenite did not decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…After oxidation treatments, chalcopyrite is aggressively oxidized, resulting in a decrease in CuFeS 2 floatability due to the formation of hydrophilic oxidation products on its surface [13,69,74,75,78].…”
Section: Cu Depressant Feed Results Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…After oxidation treatments, chalcopyrite is aggressively oxidized, resulting in a decrease in CuFeS 2 floatability due to the formation of hydrophilic oxidation products on its surface [13,69,74,75,78].…”
Section: Cu Depressant Feed Results Featuresmentioning
confidence: 99%
“…MoS 2 was also oxidized, and on its surface, oxidation products (e.g., MoO 3 ) were formed; however, MoO 3 is highly soluble under alkaline conditions, so its effect on MoS 2 floatability becomes negligible under typical Cu-Mo flotation conditions (pH > 9) [13,74,75,78].…”
Section: Cu Depressant Feed Results Featuresmentioning
confidence: 99%
“…The electrical resistivities of chalcopyrite and molybdenite are 234 Ω and 1.2-1.5 MΩ, respectively, which means that chalcopyrite is more electrochemically active than molybdenite is [78]. From the difference in the minerals' electrical resistivity, Miki et al [78] attempted to apply electrolysis, a technique that applies a fixed potential in which mineral undergoes oxidation process(es) to selectively render the chalcopyrite surface hydrophilic. Anodic polarization results at an applied potential of 1.2 V showed that a high current density of chalcopyrite electrodes (around 0.4 mA/m 2 ) was observed, indicating that the oxidation of chalcopyrite was actively progressed, as shown in the following equation:…”
Section: Electrolysis Oxidationmentioning
confidence: 99%
“…Afterwards, contact angle measurements were carried out using a goniometer (Dropmaster 300, Kyowa Interface Science Co., Ltd., Saitama, Japan). The contact angle was measured using the bubble captive method following the procedures described in previous work [17,18].…”
Section: Contact Angle Measurementsmentioning
confidence: 99%